Evidence for persistence of the SHIV reservoir early after MHC haploidentical hematopoietic stem cell transplantation - Lucrezia Colonna (Nature Portfolio, 2018)
Allogeneic hematopoietic cell transplantation (allo-HCT) has led to the cure of HIV in one individual, but the underlying mechanisms are unclear. Here, the authors present a model of allo-HCT in SHIV-infected nonhuman primates and show that the SHIV reservoir persists in multiple tissues early after transplantation.